The Hybridized Public Sphere: Asian American Christian Ethics, Social Justice, and Public Discourse - Pae, K. Christine (Journal of the Society of Christian Ethics, 2012)
IN CRITICALLY ANALYZING THE DEADLY VIPER CONTROVERSY AND MARY Queen of Vietnam Catholic Church's social activism in the aftermath of Hurricane Katrina, we consider questions concerning the (in)ability of Asian Americans to participate in public discourse in meaningful ways that spur social change while fostering solidarity with other marginalized ethnic groups in the United States. Drawing on Christian theo-ethical reflection on the racial or social identity of Jesus as a hybridized concept, we argue for a robust public discourse that recognizes Asian Americans as a social group without succumbing to the ghettoization of Asian American identity or a withdrawal from engagement with other justice-seeking social groups. In doing so, we look toward constructive modes of public discourse carried out by multiple counterpublics that both give voice to the Asian American community and open the space for collaboration across ethnic, racial, class, religious, and national boundaries.